The Silent Sea: The Legal Lacuna of Sedentary Activities in the Archipelagic Sea Lanes under UNCLOS - Mahardhika, Nur Gemilang; Kushay, Ahmad; Nasution, Arief Hasanul Husnan (Legality : Jurnal Ilmiah Hukum, 2026)
This article maps the legal gap on provisions regarding sedentary activities on Archipelagic Sea Lanes (ASLs) under UNCLOS and subsequently charts the fairway of their governance. ASLs, already an almost uncharted regime of UNCLOS on its own, offers two freedoms for states users and archipelagic alike to enjoy: navigational rights and the consequent right to conduct sedentary activities those that are not in motion but maintain a static presence within the lanes. While the law of ASLs passage under UNCLOS is rather sufficiently defined, the Convention provides little guidance on how sedentary activities should be treated. This paper turns its attention to that silence. What will become of silent underwater activities, including cable-laying, surveillance, marine scientific research, or the unmoving presence of a submarine, which take place within these sea lanes, not as passage but as position? Article 53 of UNCLOS lies at the base of this inquiry, with its notable omission of non-navigational uses of ASLs. Through a close contextual reading of the Convention, reflected by state practice, the paper surfaces the following question: do sedentary activities fall within the scope of passage granted in ASLs, or are they subject to the sovereignty of the archipelagic state? Focusing on Indonesia, the world's largest archipelagic nation, the paper examines how sovereignty is asserted over both movement and stillness. It explores the legal lacuna in situations where the sea is not merely passed through but also silently dwelled within. The paper contributes to discussions surrounding ASLs by shedding light on them as stretches of maritime corridors where neither freedom of navigation nor sovereign control is properly articulated. This paper then concludes that this silent sea is where Indonesia is expected to take the helm in recasting the advancement of maritime law in three stanzas: devising its own domestic legal reform, regional cooperation, and international legal stratagem.